Cognotoxemia: endotoxemia and gender predict changes in working memory performance in healthy adults - McDonnell, Sally C.; Graham-Engeland, Jennifer E.; Sliwinski, Martin J.; Engeland, Christopher G.; Knight, Erik L. (Frontiers in Neuroscience, 2024)
IntroductionExamining the contribution of peripheral systems to cognitive function under healthy circumstances may improve our understanding of the systems that confer risk or resilience in diseased states. Endotoxemia—a pro-inflammatory response to the translocation of bacteria that reside in the gut on other sources (e.g., respiratory tract; infection) into the blood—was hypothesized to relate to worsened cognitive functioning. Gender was explored as a moderator.MethodsA sample of 162 healthy adults (25–65 years old) provided plasma, from which a measure of endotoxemia was determined [i.e., the ratio of lipopolysaccharide binding protein (LBP) to soluble cluster of differentiation 14 receptors (sCD14)]. Participants performed an array of laboratory and ambulatory cognitive tasks at three timepoints, each separated by 9 months. Two sets of multilevel models were used: Prospective models, linking endotoxemia at baseline with changes in cognition across time, and coupling models, which examine correlations of endotoxemia with cognition across time.ResultsA prospective model indicated lower levels of endotoxemia at baseline predicted improvements in working memory across the three timepoints; higher levels were associated with no change in cognitive performance. Gender was not found to modulate this finding. Interestingly, a coupling analysis of endotoxemia and gender across time showed that in men, those with higher endotoxemia performed better at the working memory task overall; in women, working memory performance was similar regardless of endotoxemia level.ConclusionThis work provides initial evidence that endotoxemia may be associated with a dampening of improvement in working memory, improvement consistent with practice effects, which should be expected in a sample of healthy, relatively young adults. The findings also provide preliminary evidence that, at least for men, higher degrees of endotoxemia are not inherently negative, and may link with short term positive outcomes for working memory.